Characterizations of Lavender Flowers Extracts and Study of their Effects on Peroxidase Activity and Some Microorganisms - Falah S. Al-Fartusie (Journal of Global Pharma Technology, 2016)
Herbal medicinal plants have been used traditionally to treat diseases in addition to commercial use. Therefore, this study is designed to extract the most important components of lavender flowers herbal and study their biological activities against some important species of bacteria and fungi as well as against peroxidase activity. The study also includes a description of Lavender flower extract using UV-Vis and GC-MS techniques. In this study, three extracts (ethanolic, cold aqueous and hot aqueous extracts) were prepared by maceration (1gm/50ml solvent). UV-Vis spectroscopy was revealed peaks embedded in a significant functional range (200-400) nm, which may be attributed to unsaturated functional groups and hetero atoms (S, N, O). The results showed an inhibitory effect of the cold and hot aqueous extracts on the activity of peroxidase. Kinetic study demonstrated that the cold extract caused a non-competitive inhibition while hot extract caused a mixed type inhibition. The kinetic parameters obtained by Lineweaver-Burk plot, in the presence and absence of lavender extracts respectively, indicated that the Km values were (0.0007, 0.001) mM while Vmax values were (95.23, 125) U/L for cold aqueous extract, while the Km values were (0.0028, 0.003) mM, and Vmax values were (80.64, 112.5) U/L for hot aqueous extract. Antibacterial and antifungal effects against isolates in our study showed that ethanolic extract is more potent than aqueous extracts which could be predominantly the result of highly account of active phenolic compounds that presence in Lavender herbal ethanolic extract. The results of the current work support the traditional use of the studied plant and suggest that some botanical extracts, particularly ethanolic extract, have compounds with antibacterial properties that can be used as antibacterial agents in new drugs to treat infectious diseases caused by pathogens. The most effective extracts can be subjected to therapeutic antibacterial isolation and further medical evaluation.Keywords: Lavender; GC-MS; UV-Vis; Peroxidase; Antibacterial; Antifungal.